THE IMF IN GEORGIA: EVALUATING THE FUND’S UNIQUE VISION OF ECONOMIC SUCCESS - TCHANTOURIDZÉ, Lasha (CENTRAL ASIA AND THE CAUCASUS, 2005)
Many things have changed in Georgia after the Rose Revolution of November 2003. Certain changes are very positiveand praiseworthy, such as the abolition of deeply corrupt and universally hated traffic police, and its replacement with the Western style patrol police. Reforms in the armed forces are also heading toward a positive direction. However, the economy does not seem to be the new government’s priority. The leader of the Rose Revolution and the current president of Georgia Mikhail Saakashvili has made it clear a number of times that he was not interested in solving economic problems of the country as much he was interest-ed in dealing with security and defense issues.hen presenting a newly composed government in February 2005, Saakashvili was quoted by saying: “I can build the army, I can build the police, but development of the economy is up to the entire society.”1 Prior to that President of Georgia voiced similar sentiments at his address to the country’s parliament. 2 Indeed, compared to reforms in the military and law enforcement agencies economic reforms in Georgia have fallen far behind. This was partially acknowledged by Saakashvili in his above-mentioned address to the Parliament.